Guardian of the presidency : the legacy of Richard E. Neustadt - Dickinson, Matthew J.; Neustadt, Elizabeth A. (Washington, D.C. : Brookings Institution Press, 2007)
"Richard Neustadt's former colleagues and students celebrate the rich and diverse contributions he made to political and academic life in the United States and beyond"--Provided by publisher
Foreword / Doris Kearns Goodwin -- Preface -- "Placing" Richard E. Neustadt / Ernest R. May -- Practicum on the presidency, 1946 to 1953 / Matthew Dickinson -- Scholar-activist as guardian : Dick Neustadt's presidency / Charles O. Jones -- Avoiding the hazards of transition : Neustadt's lessons / Harrison Wellford -- Two of JFK's aides remember Kennedy's Machiavelli / Theodore C. Sorenson and Arthur Schlesinger, Jr. -- An American in England / Anthony King -- Was Neustadt a journalist, too? / Jonathan Alter -- Tribute to a teacher / Al Gore -- Masterful mentor / Harvey V. Fineberg -- Institution builder / Graham Allison -- Neustadt in Brazil / Eric Redman -- Afterword : a personal reminiscence / Elizabeth A. Neustadt -- Appendix : Letter to Helena Kerr do Amaral, June 15, 2003 -- Letter to President Lyndon B. Johnson, January 13, 1968, with attachment -- Memorandum to Lyndon B. Johnson from John P. Roche, January 18, 1968.
Includes bibliographical references (pages 205-207) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Neustadt, Richard E; Harvard University -- Faculty -- Biography; Neustadt, Richard E; Harvard University; Political scientists -- United States -- Biography; Political consultants -- United States -- Biography; Politologues -- États-Unis -- Biographies; Conseillers politiques -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Political; POLITICAL SCIENCE -- History & Theory; POLITICAL SCIENCE -- American Government -- Executive Branch; Political consultants; Political scientists; Universities and colleges -- Faculty; United States; collective biographies; Biographies; Biographies; Biographies